Flow injection spectrophotometric determination of tetracycline in a pharmaceutical preparation by complexation with aluminium(III) - Saisunee Liawruangrath (2018)
A rapid flow injection (FI) spectrophotometric procedure for tetracycline determination is described. It is based on the injection of a 100 μl sample solution containing tetracycline into merged streams of aluminium(III) chloride (0.01 mol l-1) and Tris-buffer in the presence of KCl (0.06 mol l-1), pH 7.0, with the same optimum flow rate of 3.2 ml min -1. A yellow Al(III)-tetracycline complex was monitored at 376 nm. The flow injection system and the experimental conditions were optimized by means of the univariate method. The procedure was applied to the determination of tetracycline in pharmaceutical preparations with a high sampling rate of at least 165 h-1. A high precision with a relative standard deviation was obtained less than 0.72 and 0.30% of 5.0 and 10 μg ml-1 (n = 11), respectively. The detection limit (3σ) and the quantification limit (10σ) were 0.07 and 0.72 mg l-1, respectively. There were no interference effects from traditional excipients in the dosage forms when the method was applied to pharmaceutical preparations. The matrix effect could be reduced by the standard addition method. 2006 © The Japan Society for Analytical Chemistry.